Studi Putusan Hakim tentang Penetapan Isbat Nikah di PA Kuningan : (Studi Kasus No. 414/Pdt.P/2022/PA.Kng dan No.350/Pdt.P/2022/PA.Kng) - Muhsin Thaha, Muzakkir; Muhamad Yusuf, Rizal (Sekolah Tinggi Ilmu Syariah Husnul Khotimah, 2024)
The submission for marriage confirmation (isbat nikah) at the Kuningan Religious Court (PA) is a legal process that tests the validity of a marriage. In this process, several cases resulted in various decisions; some were accepted as in the case with case number Number.414/Pdt.p/2022/PA.Kng and some were rejected as in the case with case number Number.350/Pdt.P/2022/PA.Kng . This study aims to analyze the decisions and considerations of judges in cases Number. 414/Pdt.P/2022/PA.Kng and Number. 350/Pdt.P/2022/PA.Kng. In addition, this research will also examine the analysis of Islamic law on the decisions and considerations of judges in the two cases. This research uses a qualitative method with the type of field research and is supplemented by library research data in the form of documents of judges' decisions regarding marriage confirmation cases. Data collection techniques using interviews and documentation. The results of this study First, in determination the case Number. 414/Pdt.P/2022/PA.Kng, the panel of judges granted the petition for isbat nikah, declared the validity of the marriage between applicant I and applicant II which took place on November 11, 2009, and determined the cost of the case in the amount of Rp. 420,000.00. However, in decision Number. 350/Pdt.P/2022/PA.Kng, the panel of judges declared the petition inadmissible and imposed court costs of Rp. 320,000 on the first and second petitioners. Second, the decision in case Number. 414/Pdt.P/2022/PA.Kng is considered appropriate and followed the rules of Islamic law because the applicant has fulfilled the conditions and pillars of marriage in Islam and followed the procedures applicable in the Religious Court. As a result, the petition for marriage confirmation submitted was accepted. Meanwhile, in case Number. 350/Pdt.P/2022/PA.Kng, the decision of the panel of judges was also considered appropriate and followed Islamic law because the first applicant did not attend the trial, which led to the rejection of the application.